A paradigm shift in the concept of arrhythmogenic cardiomyopathy: expanding the clinical and genetic spectrum, new diagnostic criteria for left ventricular phenotypes - T. G. Vaikhanskaya; L. N. Sivitskaya; T. V. Kurushko; T. V. Rusak; O. D. Levdansky; N. G. Danilenko; O. G. Davydenko (Российский кардиологический журнал)
Recent multicenter studies using high-tech cardiac imaging and novel translational technologies have shown that cardiac fibrofatty replacement, characteristic of arrhythmogenic cardiomyopathy (ACM), is observed in both ventricles; left ventricular (LV) involvement may be minimal, on par with the right ventricle (RV), or dominant. In 2019, the Heart Rhythm Society (HRS) proposed a new approach to the assessment of arrhythmic and genetic diseases with the inclusion of new phenotypes — left-dominant ACM and biventricular ACM. In 2020, to improve the diagnosis of left ventricular phenotypes, European experts revised ACM criteria (based on the 2010 ITF criteria), which are called the Padua criteria.The presented article highlights the clinical and genetic aspects of the new concept and the difficulties in ACM diagnosis, the practical experience of using new diagnostic algorithm. To help practitioners, step-by-step differential diagnosis and risk stratification of right and left ventricular phenotypes are presented using clinical examples (leftdominant ACM with a pathogenic variant in the LMNA gene; right-dominant ACM associated with a desmoplakin gene mutation, with predominant RV and moderate LV involvement; and an isolated RV ACM associated with a mutation in the plakophilin 2 gene).